THE SUSTAINABILITY OF SPORT-SPECIFIC CLASS IN SMA NEGERI 4 OF TEGAL CITY - iswoyo, Tri (International Journal Pedagogy of Social Studies, 2018)
The main objectives of the research were to understand and to analyze 1) the sustainability of sport-specific class in the 4th Public Senior High School (SMA N 4) of Tegal City. This study was a qualitative research with descriptive approach. Data were collected through observation, document analysis, and interview. The results of the research were as follows. 1) The sport-specific class was active during 2013-2016 and closed in the fourth year in 2016/2017. Considering the result of research, it could be concluded that sport-specific class has run poorly with some achievements running fairly well for 3 years with after-school achievement building conducted, but it was closed in the 4th year due to limited fund and policy changed by the government.Keywords: Class, sport, achievementÂ